Factors affecting the formation of investment funds portfolios – A field study from the perspective of Saudi financial services companies – - Aljshmah, Azizah Mesfer Dafer (Journal of Economic, Administrative and Legal Sciences, 2021)
The aim of the research is to identify the impact of the factors affecting the formation of investment funds portfolios: a field study from the perspective of Saudi financial services companies. The researcher adopted the descriptive and analytical approach. For the purpose of data collection, the questionnaire was used. The research community included all workers in the field of forming investment portfolios in companies Saudi financial services, and a random sample representing the community was selected, amounting to (159) employees, and the research reached several results, including that the expected financial return and the risks associated with it have an impact on the formation of the investment fund portfolio with a high rate of 82.27%, and it was found that there is a positive impact of the laws. Legislation on forming a portfolio of investment funds at a high rate of 81%, and it was found that there is a positive impact of economic and investment conditions on forming a portfolio of investment funds at a high rate of 80.36%. The research recommended the need to pay attention to the rate of return on investment and disclose it to encourage subscribers to do so, and job opportunities should be opened to reduce Unemployment rates and inflation influence the composition of the investment fund portfolio.
Keywords: Financial Services; Portfolio; Investment Funds; risk